SULFONYLUREA INTOXICATION AT A TERTIARY CARE PAEDIATRIC HOSPITAL - Glatstein, Miguel; Garcia–Bournissen, Facundo; Scolnik, Dennis; Koren, Gideon (Journal of Population Therapeutics and Clinical Pharmacology, 2018)
BackgroundUnintentional poisoning with sulfonylurea hypoglycaemic drugs is a serious danger to infants and children, as the ingestion of relatively small amounts can be fatal. Although the administration of octreotide is considered effective in patients that remain hypoglycaemic despite glucose administration, experience in children is limited. MethodsA retrospective chart review of the clinical features of all children following sulfonylurea ingestion presenting between April 2001and November 2008 at the Hospital for Sick Children in Toronto. ResultsTen children were identified with sulfonylurea exposure; six were classified as suspected ingestion and four had confirmed signs of sulfonylurea overdoses (mean age: 8.2 years; range 1.5 – 15). All four patients with confirmed ingestion were exposed to glyburide and developed severe hypoglycaemia; two were toddlers and two teenagers. Ingestion was accidental in the case of the toddlers, and suicidal attempts in the case of the adolescents. All patients were initially treated with glucose infusions. Both toddlers also received octreotide with favourable response and no rebound hypoglyacemia. The two teenagers were treated only with prolonged glucose infusions; in both cases rebound hypoglycaemia and increased glucose requirements were observed. DiscussionGlyburide-induced hypoglycaemia was pronounced in all patients identified. Treatment with octreotide proved effective in the 2 infants treated, agreeing with the limited experience reported to date in the literature, and suggesting that octreotide should be considered the treatment of choice in children.